Early Screening of Pregnant Who Risk of Gestational Diabetes as An Effort to Prevent Stunting Births in Coastal Areas - Yesi Hasneli; Zahtamal Zahtamal; Yunisman Roni; Syeptri Agiani Putri (Indonesian Journal of Global Health Research, 2024)
Stunting is a condition of growth failure in children due to chronic malnutrition during growth and occurs from the womb to the age of two years which has an impact on the physical, cognitive, social development of children. One of the causes of stunting is pregnant women who suffer from Gestational Diabetes. Objective: To conduct an early examination of pregnant women at risk of gestational diabetes in coastal areas. Method: Descriptive with purposive sampling approach. Data collection techniques, namely: Determine the research problem followed by a literature study. The implementation stage of the study was carried out by examining temporary blood sugar, blood pressure, weight, height, abdominal circumference, and arm circumference. Furthermore, a pretest was conducted to assess the level of knowledge of pregnant women regarding the prevention of stunting and understanding related to gestational diabetes. Data analysis with univariate analysis. Results and Discussion: The age of most respondents was 20-35 years (80.8%), Real-time Blood Sugar: > 125 mg/dL (30.7%), 101-125 mg/dL (40.4%) and < 101 mg/dL (28.8%). Systolic Blood Pressure was mostly in the range of 90-120 mmHg (57.7%), Diastolic Blood Pressure 60-90 mmHg (86.5%). The Body Weight of most respondents was 35-60 Kg (55.8%), Respondents Height was 151-168 cm (53.8%), Abdominal Circumference about 92-107 cm (61.5%) and Arm Circumference was 21-27 cm (63.4%). Conclusions: Gestational diabetes can be one of the factors causing the birth of stunted children. Therefore, early examination is needed in pregnant women to find out health problems so that they can be prevented as early as possible such as conducting examinations, blood sugar, blood pressure, weight, height, arm circumference and conditions during pregnancy. Suggestion: Early detection of pregnant women is very important in health facilities such as health centers and hospitals. This right can determine the health condition of pregnant women and identify health problems early, so as to prevent complications. Efforts that can be made include managing a healthy diet, maintaining nutrition for the fetus during pregnancy and are expected to prevent the risk of gestational diabetes complications such as the birth of stunted children.